1957
DOI: 10.1042/bj0660065
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of porphyrins by cell suspensions of Tetrahymena vorax: effect of members of the vitamin B group

Abstract: in view of the finding that this compound readily undergoes rearrangement in alkaline solution to 16-oxo-oestradiol-17,B there can be little doubt that the KC-5 previously isolated by Marrian et al. (1957) was indeed a mixture of 16oc-hydroxyoestrone and artifactually produced 16-oxo-oestradiol-17 P as was The authors are grateful to the Medical Research Council for a grant from which the expenses of this work were defrayed. They are also grateful to their colleague Dr J. W. Minnis, who carried out all the mic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
1
0
5

Year Published

1958
1958
1983
1983

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(6 citation statements)
references
References 25 publications
0
1
0
5
Order By: Relevance
“…Shemin & Wittenberg (1951) suggested that it might be succinyl-coenzyme A (succinyl-CoA) even before the isolation of this substance by Sanadi & Littlefield (1953); but little supporting evidence was obtained for this idea. Strong, but indirect evidence that coenzyme A is involved in the synthesis of 8-aminolaevulic acid comes from the study of haem and porphyrin formation in pantothenate-deficient ducks (Schulinan & Richert, 1957) and Tetrahymena vorax (Lascelles, 1957). Coenzyme A produces also a stimulation of activity in the system studied by Laver et al (1958); but all attempts to determine its role in this reactionwere unsuccessful, and indeed no 8-aminolaevulic acid was formed when synthetic succinyl-coenzyme A was substituted for succinate or a-oxoglutarate.…”
mentioning
confidence: 99%
“…Shemin & Wittenberg (1951) suggested that it might be succinyl-coenzyme A (succinyl-CoA) even before the isolation of this substance by Sanadi & Littlefield (1953); but little supporting evidence was obtained for this idea. Strong, but indirect evidence that coenzyme A is involved in the synthesis of 8-aminolaevulic acid comes from the study of haem and porphyrin formation in pantothenate-deficient ducks (Schulinan & Richert, 1957) and Tetrahymena vorax (Lascelles, 1957). Coenzyme A produces also a stimulation of activity in the system studied by Laver et al (1958); but all attempts to determine its role in this reactionwere unsuccessful, and indeed no 8-aminolaevulic acid was formed when synthetic succinyl-coenzyme A was substituted for succinate or a-oxoglutarate.…”
mentioning
confidence: 99%
“…Διά τόν σχηματισμόν της αΐμης, α-ό£υγλουταρικόν όξύ έκ τοϋ κύκλου του Krebs, ένοΰται μετά συνενζύμου Α καί σχηματίζεται ήλε κτρικός θειοεστήρ τοϋ συνενζύμου Α. Έν συνεχεία ò θειοεστήρ ούτος μετά γλυκίνης σχηματίζει, μέσω ήλεκτρογλυκίνης, δ-άμινολεβουλινικόν όξύ (δ-ALA) τη καταλυτική δράσει της συνθετάσης ö-ALA (Kappas καί συν. 1968, Lascelles 1963, Gibson καί συν. 1955.…”
Section: Th Annual Meeting Of the European Association For The Study Ofunclassified
“…Τα λιποειδή και οι περισσότερες πρωτεΐνες παράγονται γιά εσωτερική χρήση του κυττάρου, ο πότε μπορούν και να ανιχνευθούν σ'αυτό. Η Τ,ργΓϊίοηπϊεδιαθέτετι τις μεταβολικές πορείες των θηλαστικών (2) και συγχρόνως βιοσυνθέτει πολύπλοκες, εξειδικευμένες ενώσεις όπως αιμοσφαι ρίνη, (19,20 ) > σεροτονίνη, (21,22 ), ισταμίνη, σωματοοτατίνη, κατεχολαμίυες, (23), β-ενδορφίνη (24,25), ρελαξίνη (26) και προσταγλανδίνες (27).…”
Section: H T Pyriformis οαν πρότυπο οΰοτημα μελέτης των μεμβρανών των ευκαρυωτικων κυττάρωνunclassified